Rodent home cage monitoring for preclinical safety pharmacology assessment: results of a multi-company validation evaluating nonclinical and clinical data from three compounds - Sillito, R. R.; Sutherland, J.; Milne, A.; Giuliano, C.; Sigfridsson, C.; Rolf, M.; Cherian, A. K.; McClafferty, M.; Rossman, E. I.; Teuns, G.; Armstrong, J. D.; Holmes, A. M. (Frontiers in Toxicology, 2025)
IntroductionThe presence of central nervous system (CNS) safety concerns during early clinical testing that were not picked up in standard preclinical assessment is a major cause of attrition in drug development. It is also very expensive, time consuming and potentially dangerous for clinical trial participants. Rodent home cage monitoring approaches have previously been shown to deliver significant animal welfare benefits through group/social housing, minimal interventions avoiding stress that can confound results, and in some cases also animal reduction benefits with the multiplex data acquisition requiring fewer total animals. Here we looked at the utility of home cage monitoring to uncover potential CNS effects not identified using standard safety pharmacology tests.MethodWe hypothesised that longitudinal behavioural assessment–by capturing non-evoked behaviour and reducing sampling artefacts–would be more sensitive to adverse reactions in preclinical animal models (i.e., rodents). To test this, we selected three compounds which previously passed standard safety tests but were failed later including two during clinical trials. We validated the general methodology for using home cage monitoring in safety assessment study designs from single doses to repeat dosing for up to 4 weeks. We then re-tested the three compounds in single dose studies.Results/DiscussionWe showed that the methodology fits well with standard study designs. More importantly we uncovered significant findings in all three compounds that were not observed in the original classic safety pharmacology tests. The lack of such effects observed in standard preclinical assessment likely reflects functional differences between the limited observational snapshots characteristic of this approach and the more comprehensive temporal resolution enabled by continuous home cage monitoring.